CAZRI Ber 2018: New early variety of ber - Meghwal, P R; Vashistha, B B; Singh, Akath; Prasad, R N; Singh, S K (Indian Horticulture, 2020)
CAZRI Ber 2018 released by ICAR-Central Arid Zone Research Institute (Jodhpur), in 2018, is the earliest variety of ber in North India. It is a high yielder with an average fruit yield of about 61 kg/plant under rainfed condition (300-400 mm). Mean plant height is 2-3 m, spreading growth habit, mean fruit weight- 19.26 g, fruit size 3.19cm × 3.13cm (L×W), mature fruit colour-greenish yellow, fruit shape round, pulp, stone ratio 12.33, TSS 18.83°Brix, pulp acidity 0.51%, and vitamin C content is 50.73 mg/100g.